2018
DOI: 10.5664/jcsm.6884
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea in Patients Hospitalized With Acute Ischemic Stroke: Underrecognition and Associated Clinical Outcomes

Abstract: Prevalence of sleep apnea in our study was low, likely because of clinical underrecognition. Despite having more cardiovascular disease, the patients with acute stroke and sleep apnea had less severe neurological injury and lower unadjusted mortality than those without a history of sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
1
25
2
Order By: Relevance
“…Primary studies: Six additional primary studies of class II or III quality were identified [110][111][112][113][114][115].…”
Section: What Is the Frequency Of Sdb In Stroke Patients?mentioning
confidence: 99%
See 2 more Smart Citations
“…Primary studies: Six additional primary studies of class II or III quality were identified [110][111][112][113][114][115].…”
Section: What Is the Frequency Of Sdb In Stroke Patients?mentioning
confidence: 99%
“…The frequencies for the different AHI cut-offs were found: AHI >5 in 70.4% (95% CI 62. [95,[110][111][112][113][114][115]. Most studies published did not find any relationship between topography of stroke and frequency/severity of SDB, although few reports suggested an association between central SDB and supratentorial, and obstructive SDB and infratentorial stroke [31].…”
Section: Overview Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…This finding may also suggest a cardioprotective role of OSA, which may attenuate the development of ST-elevation myocardial infarction (STEMI), perhaps through IPC [17]. In patients with OSA hospitalized because of an acute ischemic stroke, less severe neurological injury and lower unadjusted mortality rates were found than in those without a history of OSA [18]. Also, cardiac arrest survivors with OSA had better unadjusted survival rates and favorable adjusted neurological outcomes at discharge than those without OSA [19].…”
Section: Potential Involvement Of Ipc In Osa Patients With Acute MI Amentioning
confidence: 90%
“…The severity of the IH and the hypoxemia in OSA are determined by the number of the hypoxic events per hour of sleep, termed Apnea-Hypopnea Index (AHI). It mostly ranges from a cutoff point of 10 events per hour of sleep for normal breathing to mild (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and severe OSA (>30 events per hour of sleep). In severe patients, blood oxygenation levels can intermittently drop to as low as 60%.…”
Section: Introductionmentioning
confidence: 99%